Cassino to the Alps - Fisher, Ernest F., 1918- (Washington, D.C. : Center of Military History, United States Army : For sale by the Supt. of Docs., U.S. Govt. Print. Off., 1977)
Continues the account of operations in Italy from Operation DIADEM and the capture of Rome to the negotiations for the surrender of German armies in Italy.
The spring offensive -- Spring in Italy, 1944 -- Preparing for a new offensive -- Diadem's first day, 11 May -- Collapse of the Gustav Line -- Breakthrough on the Southern Front -- Breakout from the beachhead -- The Anzio beachhead -- The first day -- Breakout from the beachhead -- Drive to Rome -- Stalemate along the Caesar Line -- Breaking the stalemate -- The fall of Rome -- Rome to the Arno -- Interlude in Rome -- Pursuit North of Rome -- The pursuit ends -- End of the campaign in Central Italy -- Along the Arno -- The Gothic Line offensive -- Planning for the offensive -- The Gothic Line offensive begins -- Battle for the pass -- A diversionary operation -- In the Northern Apennines -- From ridge to ridge -- Toward a winter stalemate -- Stalemate in the mountains and on the plain -- Through the winter -- The last offensive -- Strategies and plans -- Breakthrough on the Eighth Army front -- Breakthrough on the Fifth Army's front -- Pursuit to the Alps -- Race for the Po -- To the Alps -- The capitulation -- An assessment.
Includes bibliographical references and index.
Keywords: 1939-1945; World War, 1939-1945 -- Campaigns -- Italy; Military campaigns; Italy -- History -- German occupation, 1943-1945.; History